Accidental placement of hemodialysis catheter tip in the right internal mammary vein: a case report - Montepío, Rafael Parcarey; Gonzales, Bernardo Moguel; Villa, Jose Daniel Juarez (Journal of Clinical Nephrology, 2022)
Hemodialysis catheter placement, particularly Internal Jugular Catheter insertion, is a very common procedure for patients who require urgent access to renal replacement therapy. Most of these procedures are done under ultrasound guidance as recommended by KDIGO 2019 vascular access guidelines. However, catheter tip misplacement can still occur even in the experts’ hands and despite the use of ultrasound. In this case report, we will discuss a hemodialysis catheter tip placement in the right internal mammary vein and how we managed it.